2012
DOI: 10.1074/jbc.m111.275354
|View full text |Cite
|
Sign up to set email alerts
|

The C Terminus of Bax Inhibitor-1 Forms a Ca2+-permeable Channel Pore

Abstract: Background: Evolutionary conserved Bax inhibitor-1 (BI-1) protects against ER stress-mediated apoptosis. Results: We identified a Ca 2ϩ -permeable channel pore in the C terminus of BI-1. Critical pore properties are an ␣-helical structure and two aspartate residues conserved among animals, but not among plants and yeast. Conclusion: C-terminal domain of BI-1 harbors a Ca 2ϩ -permeable channel pore. Significance: BI-1 has Ca 2ϩ channel properties likely relevant for its function in ER stress and apoptosis. Bax … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
102
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(114 citation statements)
references
References 50 publications
(79 reference statements)
10
102
0
2
Order By: Relevance
“…These results are well in line with previously reported effects of BI-1 in the control of the ER Ca 2+ content. [6][7][8]10 Also, structural evidence obtained from a bacterial homolog of BI-1 just demonstrated that BI-1 is indeed a Ca 2+ leak channel with an evolutionarily conserved pH sensor. 11 Bar graphs show the mean ± S.E.M., n = 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are well in line with previously reported effects of BI-1 in the control of the ER Ca 2+ content. [6][7][8]10 Also, structural evidence obtained from a bacterial homolog of BI-1 just demonstrated that BI-1 is indeed a Ca 2+ leak channel with an evolutionarily conserved pH sensor. 11 Bar graphs show the mean ± S.E.M., n = 3.…”
Section: Discussionmentioning
confidence: 99%
“…5 In mammalian cells, BI-1's antiapoptotic function is most pronounced in paradigms of ER stress 6 and involves changes in the amount of Ca 2+ that can be released from intracellular stores. 6,7 BI-1 is a highly hydrophobic protein that forms a Ca 2+ pore responsible for its Ca 2+ leak properties 8 and is the founding member of a family of six proteins with similar properties. 9 The increase in the ER Ca 2+ leak mediated by BI-1 is blocked at a more acidic pH 10 -a function recently corroborated by a structural analysis of a bacterial homolog of BI-1.…”
mentioning
confidence: 99%
“…Five million MEF cells were lysed in RIPA buffer and 30 g of total protein was loaded on Tris-Acetate gels (Invitrogen) in the presence of urea sample buffer [9]. The proteins were transferred on a PVDF membrane and blotted for IP 3 R1 [25], IP 3 R3 (BD Biosciences), SERCA2b [26] or non-muscle myosin IIA (Abcam) for loading control.…”
Section: Western Blotmentioning
confidence: 99%
“…The assays were performed as previously described [25,27], except that different buffers were used for proper pH control in the efflux medium (imidazole for pH 6.8 and 6.2; MES for pH 5.8 and acetate for pH 5.2). In the experiments in which a peptide corresponding to the C-terminal Ca 2+ -channel pore of BI-1 was used, the peptide (CTP1) was added acutely at a concentration of 40 M, well above the EC 50 for provoking a Ca 2+ flux (32 M, [9]). Purity (>80%) was verified by mass spectrometry (ThermoFisher, Germany).…”
Section: Ca 2+ -Flux Assaysmentioning
confidence: 99%
See 1 more Smart Citation